The sky at night : easy enjoyment from your backyard - Hunter, Tim B. (University of Arizona Press, 2023)
"This is a guidebook for the naked eye viewing and enjoyment of the night sky. The book assumes the reader is literate but not particularly knowledgeable about the sky. Emphasis is on naked eye viewing with an occasional reference to using binoculars or a small telescope. Any time of day or night is fair game for an observing session, though there is an emphasis on early evening viewing, often in the evening twilight, as that is more convenient for most working people. However, the book does not shy away from the pre-dawn sky, and notes it is sometimes necessary to be up in the middle of the night to see something interesting or unusual. The Moon, bright stars, and constellations are described in detail not only for their appearance and viewing opportunities but also for their astronomical importance"--